La ética: Punto de encuentro de la educación ambiental y el ser profesional (2011)
This article is a review of the literature that shows the pedagogical task in shaping the person and the intentional construction of its world responsibility. Moreover, being certain that there is a need to develop a critical awareness of the relationship with the world. Environmental education connects us with the sense of existence because it promotes a relational ethic of dialogue and respects the world as the totality of our living space as people and our concrete intellectual horizon.